The evolving role of liver transplantation in managing polycystic liver disease - Afzal, Aqsa (Journal of the Pakistan Medical Association, 2025)
Polycystic liver disease (PLD) is a rare genetic condition characterised by the presence of numerous cysts throughout the liver (1). PLD was initially described in 1856 as a diseased state connected to polycystic kidney disease (PKD), and in 1925, it was suggested that PLD might exist independently of PKD. Most patients remain asymptomatic; however, some may develop clinical symptoms. The expansion of the liver and its strain on the surrounding organs cause PLD symptoms. Common symptoms of PLD include early satiety, postprandial fullness, gastroesophageal reflux, and digestive intolerance and due to these symptoms, the patient may decide to cut back on meals, which could result in severe malnutrition and weight loss (2). In extreme cases, venous drainage blockage can cause portal hypertension, along with associated symptoms such as jaundice, ascites, splenomegaly, oesophageal varices, and encephalopathy. Three types of primary therapeutic approaches are available for PLD: drug therapy, radiological or percutaneous intervention and surgery. Somatostatin analogues are recommended by the European Association for the Study of the Liver (EASL) decision-making flowchart for PLD patients who have a large number of dispersed small-to-medium-sized cysts (3). For percutaneous therapy, cyst aspiration and sclerosis are performed for patients with a single giant cyst while transcatheter arterial embolization is to embolize the branches of arteries that supply blood to cysts resulting in control of disease progression (1). Surgical procedures that include liver resection and liver transplantation, are usually considered for advanced cases. Some recent studies have brought attention to the role of liver transplantation in PLD, especially given the challenges in therapy and the requirement for successful long-term results. In this context, the results of a recent retrospective study done by Moein M et al. are worth considering. The study compared post-transplant outcomes of liver transplant recipients between 2000 and 2023, dividing the population into two subgroups. The findings highlight a notable improvement in the results of liver transplantation for PLD during the previous ten years, particularly in the 2011–2023 cohort. The prognosis shown by the graft and patient survival rates suggests that this therapeutic strategy has become a more viable course of treatment (4). Additionally, a case report by Niibek M et al. describes a patient with a large polycystic liver who underwent successful liver transplantation. The liver weighed 14,75 kg and measured 53 x 37 x 39 x 16 cm. —Continue